Analysis of the “Employee-Generated Content” Marketing Communication Strategy for Sculpt Products on TikTok - Lian Winoto; Fabianus Fensi (Journal of Social Research, 2026)
The rapid growth of social media platforms has transformed digital marketing communication strategies, requiring brands to develop more authentic, interactive, and relatable approaches to engage audiences. TikTok, as a short-form video platform, provides opportunities for fashion brands to strengthen consumer relationships through creative content strategies. SCULPT, a shapewear brand, has shifted from relying on external content creators toward an Employee-Generated Content (EGC) strategy by positioning internal employees as brand communicators. This study aims to examine how SCULPT implements EGC as a marketing communication strategy on TikTok and to identify the reasons behind the adoption of this approach. This research employed a qualitative method using in-depth interviews, observation, and documentation involving key informants, including the owner, marketing manager, social media specialist, ads specialist, and content creators. The findings indicate that SCULPT’s EGC strategy represents an Integrated Marketing Communication (IMC) practice through three main dimensions: message consistency, communication channel integration, and relationship building. The strategy maintains consistent brand messages related to comfort, product quality, confidence, and women empowerment while integrating TikTok, TikTok Shop, live streaming, campaigns, and paid advertising channels. Furthermore, employees act as brand representatives who create closer, more personal, and trustworthy interactions with audiences. In conclusion, EGC enables SCULPT to strengthen brand identity, improve audience engagement, and adapt marketing communication to the dynamic characteristics of digital media.